2015
DOI: 10.7326/m15-0166
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Risk and Informed Consent for Research on Medical Practices

Abstract: Background The U.S. Office for Human Research Protections has proposed that end points of randomized trials comparing the effectiveness of standard medical practices are risks of research that would require disclosure and written informed consent, but data are lacking on the views of potential participants. Objective To assess attitudes of U.S. adults about risks and preferences for notification and consent for research on medical practices. Design Cross-sectional survey conducted in August 2014. Setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
96
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(108 citation statements)
references
References 21 publications
12
96
0
Order By: Relevance
“…These data echo other published reports regarding MI trial enrolment. They are also consistent with evidence suggesting that patients have a preference for some form of consent in CER studies more generally and have implications in the context of recent arguments against prospective consent for these trials 19 20. At a minimum, these findings do not support a claim that enrolment without prospective consent in AMI trials investigating treatments within the standard of care can be based on preferences of patients.…”
Section: Discussionsupporting
confidence: 72%
“…These data echo other published reports regarding MI trial enrolment. They are also consistent with evidence suggesting that patients have a preference for some form of consent in CER studies more generally and have implications in the context of recent arguments against prospective consent for these trials 19 20. At a minimum, these findings do not support a claim that enrolment without prospective consent in AMI trials investigating treatments within the standard of care can be based on preferences of patients.…”
Section: Discussionsupporting
confidence: 72%
“…However, there were no significant relationships between any of the sociodemographics studied and the CTSs. Different from the participants in the previous surveys by Gaylin et al (2011) and those of a recent survey using three vignettes to assess attitudes toward informed consent (Cho et al 2015), respondents for this study were hospitalized patients, who were older, in poorer health, and more likely to have previously participated in research studies.…”
Section: Discussionmentioning
confidence: 99%
“…But if a waiver of informed consent was the only way a trial of high social value could be done, would these same investigators change their minds? Surveys conducted in the US have shown that both the public27 and patients28 who endorse written or verbal consent in low risk pragmatic RCTs change their minds if this would make the trial impractical.…”
Section: Proposed Solutionsmentioning
confidence: 99%